1985
DOI: 10.1042/cs0690153
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Morphometric Properties of Mitochondrial Populations in Human Muscle Fibres

Abstract: Two mitochondrial subpopulations were evaluated with biochemical and morphological techniques in human gastrocnemius muscle of 10 patients with peripheral arterial insufficiency and 12 control individuals. The subsarcolemmal mitochondria were released by gentle homogenization, with a recovery of 32-37%, and the intermyofibrillar by enzymic digestion and further mechanical disintegration, recovery 18-21%. The subsarcolemmal mitochondria were morphologically defined as those located within 2 micron from the sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
41
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 0 publications
10
41
2
Order By: Relevance
“…As noted by Dr Green, some studies using mitochondria from patients with PAD have shown normal function, 37,68 but others have shown abnormalities in oxidative function. 27 All of these studies must be interpreted cautiously.…”
Section: Rebuttal To the Negative Argument (Drs Brass And Hiatt)mentioning
confidence: 99%
See 3 more Smart Citations
“…As noted by Dr Green, some studies using mitochondria from patients with PAD have shown normal function, 37,68 but others have shown abnormalities in oxidative function. 27 All of these studies must be interpreted cautiously.…”
Section: Rebuttal To the Negative Argument (Drs Brass And Hiatt)mentioning
confidence: 99%
“…26,48 Yet, maximal mitochondrial respiration and activities of respiratory chain enzymes are normal in PAD 3,37,68 ; whereas they can be less than 20À30% of control values in mitochondrial myopathies. 67,74 The affirmative argument rests partly on differences in enzyme ratios (e.g.…”
Section: Rebuttal To the Positive Argument (Dr Green)mentioning
confidence: 99%
See 2 more Smart Citations
“…Pericapillary basement membrane thickening (7,8,24) and alterations of the volume density (V v ) of mitochondria (V v mito ) (1,15) are examples of ultrastructural changes in skeletal muscle in patients with CLI, the late, most severe stages of PAD. However, skeletal muscle samples from CLI patients are heterogeneous and contain large deposits of fat and connective tissue, and there is a higher proportion of degenerated fibers compared with that observed in patients with IC (11), which limits their potential to be used in quantitative investigations.…”
mentioning
confidence: 99%